Peningkatan Kemampuan Berbicara Menggunakan Metode Kooperatif Tipe NHT pada Mahasiswa Tingkat I-A PBSI Tahun Akademik 2018/2019 - Agus Darmuki; Nur Alfin Hidayati (Jurnal Pendidikan Edutama, 2019)
The purpose of this research is to improve: (1) the quality of the learning process by using the cooperative type NHT method on PBSI study program level I-A IKIP PGRI Bojonegoro and (2) speaking skills by applying the cooperative type NHT method on PBSI I-A IKIP PGRI Bojonegoro study program students. This research is a classroom action research. The subjects of this study were I-A level students with 32 students consisting of 24 female students and 8 male students and speaking skills lecturers. The object of this research is learning to speak. Data collection techniques used were observation, in-depth interviews, and document analysis. The data validity technique uses data source triangulation techniques and method triangulation. The data analysis technique used is a comparative description analysis technique and interactive analysis. This research was conducted in two cycles which included four stages, namely: planning, implementation, observation, and reflection. The results showed an increase in learning speaking skills, marked by an increase in the number of students who reached the completeness limit, namely in the first cycle there were 5 students (16%) and the second cycle 28 students (87.5%). The average value of students has increased, namely 64.1 in the first cycle and 75.3 in the second cycle. This proves that the application of the NHT type cooperative method can increase student activeness, process and learning outcomes of student speaking skills.